RANCANG BANGUN DAN SIMULASI GERBANG TOL OTOMATIS BERBASIS ARDUINO UNO DENGAN SENSOR HC-SR04 MENGGUNAKAN PLATFORM WOKWI - Akhlis Munazilin; Nur Ayu Wahyuningyati; Nurani Nurani; Putri Ilma (CV. Denasya Smart Publisher, 2026)
The increasing demand for efficient traffic management at toll gates has encouraged the adoption of automation technologies to reduce vehicle congestion and improve operational performance. This study aims to design and simulate an automatic toll gate system based on an Arduino Uno using the Wokwi simulation platform. The proposed system utilizes an HC-SR04 ultrasonic sensor to detect the presence of vehicles, a servo motor to control the movement of the gate barrier, and LEDs as visual indicators of the gate status. The research method consists of system design, programming, simulation, and functional testing. Simulation results indicate that the toll gate operates automatically by opening when a vehicle is detected within a distance threshold of ≤ 10 cm and closing automatically when the object is no longer within the detection range. All system components performed according to the designed operational scenarios. The findings demonstrate that the Wokwi platform is an effective tool for developing and testing microcontroller-based automation systems and can serve as a practical learning medium for automation and embedded systems education.